2017
DOI: 10.1177/0091415017697724
|View full text |Cite
|
Sign up to set email alerts
|

Do Financial Constraints Affect Depressive Symptomatology Among Mid-Aged and Older Adults?

Abstract: The relationship between financial constraints and depressive symptomatology among adults aged 50 and greater was examined. The mediating effect of perceived control over one's financial circumstances on this relationship was assessed. Ordinary least square hierarchical regression models were estimated using data from the Health and Retirement Study. As an aggregated measure, financial constraints were positively associated with depression in mid-age and late life, and this relationship was partially accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Fourteen studies investigated the association between debt and depression and provided empirical evidence based on high-income countries (Europe and the US) and Chile. Three studies were cross-sectional and all of them reported a positive association between debt (assessed by student debt, the occurrence of any debt, or unsecured debt) and depressive symptoms after controlling for demographic and other socioeconomic factors [ 6 , 27 , 53 ]. Eleven longitudinal studies identified by this review investigated the association between debt and depression over time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies investigated the association between debt and depression and provided empirical evidence based on high-income countries (Europe and the US) and Chile. Three studies were cross-sectional and all of them reported a positive association between debt (assessed by student debt, the occurrence of any debt, or unsecured debt) and depressive symptoms after controlling for demographic and other socioeconomic factors [ 6 , 27 , 53 ]. Eleven longitudinal studies identified by this review investigated the association between debt and depression over time.…”
Section: Resultsmentioning
confidence: 99%
“…Various measures of debt were used in the reviewed studies such as the occurrence of debt [ 26 , 27 , 53 ], the amount of debt [ 6 , 14 , 26 , 28 , 53 ], and the debt-to-income ratio or debt-to-asset ratio [ 14 , 46 , 48 ]. The debt-depression relationship varies with different operationalisations of debt with the debt to asset ratio being a more reliable predictor of depression than the total debt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has reported that financial stress is a trigger for the development of depressive symptoms among older Chinese women (Lin et al, 2011 ), and financial constraints significantly predict depression among middle-aged and older adults (Gillen et al, 2017 ). Unlike previous studies, the current study has found that household income alone was not a significant predictor of future quality of life.…”
Section: Discussionmentioning
confidence: 99%